The Effect of Self-Efficacy, Training and Work Environment on Employee Performance at PT. XYZ - Cahyani, Margiati Ayu; Febrian, Wenny Desty (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study aims to analyze the influence of self-efficacy, training, and work environment on employee performance at PT. XYZ. High self-efficacy can enhance employees' confidence in completing tasks. In addition, effective training programs and a conducive work environment are believed to support performance improvement. This study employs a quantitative method with data collection techniques through questionnaires and literature studies. The research population consists of all 627 employees of PT. XYZ, with a sample of 86 employees determined using Slovin's formula with a 10% margin of error. The results of the coefficient of determination analysis (R²) show that self-efficacy, training, and work environment influence employee performance by 62.9%, while the remaining 37.1% is affected by other variables. The partial test results indicate that each variable has a significant impact on employee performance. Furthermore, the simultaneous test confirms that self-efficacy, training, and work environment collectively have a significant influence on the performance of employees at PT. XYZ.